Envoys of abolition : British naval officers and the campaign against the slave trade in West Africa. - Wills, Mary (Liverpool studies in international slavery, 2019)
Drawing on substantial collections of previously unpublished papers, this book examines personal experiences of British naval officers employed in suppressing the transatlantic slave trade from West Africa in the nineteenth century. It illuminates cultural encounters, the complexities of British abolitionism, and extraordinary military service at sea and in African territories.